Síndrome de burnout en docentes de Educación Básica Regular de Arequipa - Arias Gallegos, Walter Lizandro (2013)
In the present we expose the results of the study about burnout syndrome incidence in a sample of 233 educators (127 male and 106 female) with an age range among 20 and 65 years old, who work in public and private schools in Arequipa City. The Maslach Burnout Inventory for Educators was applied and the results show that 93,7% of male educators has a moderate level of burnout and 6,3% has a severe level, meantime 91,5% of female teachers has a moderate level and 7,5% has a severe level of burnout. Major percentage of male teachers has higher punctuations in exhaustion, cynicism and inefficacy; than female educators. Moreover, we found significant relations (p<,000) among type of educative administration and cynicism and inefficacy. As conclusion, male teachers are more severe affected by burnout syndrome than female teachers, who dedicate to teach students in basic education level